2022
DOI: 10.1093/nar/gkac388
|View full text |Cite
|
Sign up to set email alerts
|

AlphaKnot: server to analyze entanglement in structures predicted by AlphaFold methods

Abstract: AlphaKnot is a server that measures entanglement in AlphaFold-solved protein models while considering pLDDT confidence values. AlphaKnot has two main functions: (i) providing researchers with a webserver for analyzing knotting in their own AlphaFold predictions and (ii) providing a database of knotting in AlphaFold predictions from the 21 proteomes for which models have been published prior to 2022. The knotting is defined in a probabilistic fashion. The knotting complexity of proteins is presented in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…This study presented the first crystal structure of the double knotted protein, CnTrmD-Tm1570; however, high-confidence proteins containing double knots are provided AlphaFold, and their structural analyses are deposited in AlphaKnot. 1 Thus, understanding the structure and function of knotted proteins can provide important insights into how proteins work and how they can be regulated. Overall, it still needs to be fully understood how knotted protein affects degradation, and more research is needed to clarify the relationship between these two processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study presented the first crystal structure of the double knotted protein, CnTrmD-Tm1570; however, high-confidence proteins containing double knots are provided AlphaFold, and their structural analyses are deposited in AlphaKnot. 1 Thus, understanding the structure and function of knotted proteins can provide important insights into how proteins work and how they can be regulated. Overall, it still needs to be fully understood how knotted protein affects degradation, and more research is needed to clarify the relationship between these two processes.…”
Section: Discussionmentioning
confidence: 99%
“…This study presented the first crystal structure of the double knotted protein, Cn TrmD-Tm1570; however, high-confidence proteins containing double knots are provided AlphaFold, and their structural analyses are deposited in AlphaKnot. 1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also available in Alpha-Knot database alongside with knotted proteins of 20 other proteomes at https://alphaknot.cent.uw.edu.pl. (Niemyska et al, 2022) After careful evaluation, we concluded that over 75% of the models containing knots are artifacts. However, most of the previously known knotted human proteins were correctly predicted, which shows that AlphaFold is capable of modeling structures with complicated topology (see Table S1 for details about all proteins we classified as knotted).…”
Section: Introductionmentioning
confidence: 96%